A Lys49 phospholipase A2 homologue from Bothrops asper snake venom induces proliferation, apoptosis and necrosis in a lymphoblastoid cell line - Mora Rodríguez, Rodrigo Antonio (2005)
Lys49 phospholipase A2 homologues are abundant in viperid snake venoms. These proteins have substitutions at the calcium-binding loop and catalytic center which render them enzymatically inactive; however, they display a series of toxic activities, particularly cytotoxicity upon various cell lines in vitro. In this study we explored whether myotoxin II (MT-II), a Lys49 phospholipase A2 homologue from the venom of the snake Bothrops asper, is capable of inducing various effects in a single cell type, using the lymphoblastoid B cell line CRL-8062 as a model. Cells were incubated with varying concentrations of MT-II for 24 and 48 h, time intervals that are more prolonged than the usual incubation times previously used in the characterization of this toxin. Results indicate that MT-II induces proliferation at low concentrations (0.5–5.0 μg/mL). Apoptosis was predominant at higher toxin levels (5–25 μg/mL), whereas necrosis, associated with overt plasma membrane disruption, occurred at concentrations ≥25 μg/mL, and was the predominant effect at higher MT-II concentrations (50 μg/mL). It is concluded that a single phospholipase A2 homologue can induce markedly different effects on a single cell line, depending on the concentration used, an observation that may have implications for the action of this type of venom component in vivo.